2019
DOI: 10.1108/jbim-01-2018-0046
|View full text |Cite
|
Sign up to set email alerts
|

Learn to be good or bad? Revisited observer effects of punishment: curvilinear relationship and network contingencies

Abstract: Purpose Although supplier-initiated punishment is widely used to manage distributors’ opportunism, its spillover effect on unpunished distributors (i.e. observers) within the same distribution network remains under-researched. Specifically, this paper aims to investigate the curvilinear effect of punishment severity on an observer’s opportunism, and how such an effect is contingent on the observer’s network position. Design/methodology/approach This paper uses regression analysis with survey data gathered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…However, moderate to high levels can reduce opportunism by facilitating coordination. This finding is consistent with recent evidence that punishment severity has an inverted U-shaped effect on a channel observers' opportunism (Xiao et al, 2019). In addition, the frequent use of strong coercive influence strategies produces less negative affect as it rapidly leads to compliance, thus facilitating a change in the relationship from coercion to mutually beneficial exchange (Molm, 1994).…”
Section: Theoretical Contributionssupporting
confidence: 90%
See 1 more Smart Citation
“…However, moderate to high levels can reduce opportunism by facilitating coordination. This finding is consistent with recent evidence that punishment severity has an inverted U-shaped effect on a channel observers' opportunism (Xiao et al, 2019). In addition, the frequent use of strong coercive influence strategies produces less negative affect as it rapidly leads to compliance, thus facilitating a change in the relationship from coercion to mutually beneficial exchange (Molm, 1994).…”
Section: Theoretical Contributionssupporting
confidence: 90%
“…Second, managers should understand how to use influence strategies to protect channel relationships from opportunism. When applying coercive influence, a high level is required to ensure opportunism is effectively deterred, both for a firm's partners and for channel observers (Xiao et al, 2019). Unlike other research into power in Western cultural contexts (Brown et al, 2009), this study offers evidence that coercive influence can be positive in an exchange relationship.…”
Section: Managerial Implicationsmentioning
confidence: 83%
“…A dependence power advantage is one of the most cited antecedents of opportunism in the inter-firm relationship literature (Grandinetti, 2017 ; Hawkins et al, 2008 ; Tangpong et al, 2015 ; Wang & Yang, 2013 ). Previous studies had shown that opportunism’s association with other variables could be curvilinear, for example, opportunism and performance (Lado et al, 2008 ), opportunism and goal exceedance (El Meladi et al, 2018 ), opportunism and punishment severity (Xiao et al, 2019 ), and opportunism and guanxi (Shen et al, 2019 ). Drawing on the long-term perspective of Dabholkar et al ( 1994 ) and the relationship development cycle (Dwyer et al, 1987 ), opportunism is expected to be low at the relationship initiation stage but, as the relationship develops and power relations become obvious, the partner or its agent with the higher power could easily use the power advantage to exploit the weaker partner.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…In the current study, the scope lies in the manufacturing sector, specifically a manufacturer’s interaction with its distributors and the related characteristics in the setting of manufacture-distributors (Xiao et al , 2019). The configuration of the setting is shown in Figure 2.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…The other rising paradigm treats the network embeddedness as contingent factors that affect the efficiency of channel behavior (Gao et al , 2015). For instance, Zhang and Guan (2013) proposed that network density strengthens the negative relationship between coercive power exercise and cooperation and the positive relationship between noncoercive power exercise and cooperation in the Chinese business-to-business context; Gao et al (2015) posited that while buyer-supplier relational strength strengthens the positive effect of technological diversity in supplier network on the buyer firm’s new product creativity, supplier network density weakens the relationship; Xiao et al (2019) found that the observer’s network centrality weakens the inverted U-shaped relationship between punishment severity and observer opportunism.…”
Section: Theory and Backgroundmentioning
confidence: 99%